Dinuclear zwitterionic silver(i) and gold(i) complexes bearing 2, 2-acetate-bridged bisimidazolylidene ligands. Issue 37 (6th September 2019) - Dominelli, Bruno; Roberts, Gerri M.; Jandl, Christian; Fischer, Pauline J.; Reich, Robert M.; Pöthig, Alexander; Correia, João D. G.; Kühn, Fritz E.
Abstract : Four novel dinuclear Ag(i ) and Au(i ) NHC complexes bearing two 2, 2-acetate-bridged bisimidazolylidene ligands (R = Me and iPr) of zwitterionic and metallacyclic forms are reported. Abstract : Four novel dinuclear Ag(i ) and Au(i ) NHC complexes bearing two 2, 2-acetate-bridged bisimidazolylidene ligands (R = Me and iPr) of zwitterionic and metallacyclic forms are reported. The functionalized methylene bridge of the ligands leads to water soluble complexes, which have been characterized by NMR and IR spectroscopy, elemental analysis and single crystal X-ray diffraction in the case ofLa -H2 -PF6, Ag2 (La )2, Ag2 (Lb )2 andAu2 (La )2 . Dimerization processes caused by hydrogen bonding or Ag(i )-carboxylate interactions in the solid state were observed forLa -H2 -PF6 andAg2 (La )2 . DOSY NMR experiments confirmed that both bisimidazolium salts appear as dimers in aqueous solutions, in contrast to the corresponding monomeric Ag(i ) and Au(i ) complexes. Both gold(i ) complexes form syn - and anti -isomers analogous to the reference coinage metal-based complexes. Protonation studies of the syn -isomer gold(i ) complexAu2 (La )2 were successful, whereas post-modification esterification or amidation reactions were not feasible. Additionally, decarboxylation reactions (thermally induced Krapcho- or oxidative Hunsdiecker-type) of the bisimidazolium salts were observed. Thus, the proximity of the carboxyl moiety to imidazolium/imidazolylidene rings seems to negatively affect stability and reactivity.